2017
DOI: 10.1111/bjso.12202
|View full text |Cite
|
Sign up to set email alerts
|

Is higher inequality less legitimate? Depends on How You Frame it!

Abstract: Economic inequality is increasing both globally and in various countries around the world, and such inequality has been linked to worsening health, well‐being, and social cohesion. A key predictor for whether people take action against inequality is the extent to which they perceive it as illegitimate. We investigate how two variables jointly predict the legitimization of inequality, namely the perceived magnitude of differences in economic outcomes and the way these differences are described. Two experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 49 publications
1
20
0
9
Order By: Relevance
“…But the questions about how poor they felt their ingroup to be was not included in all the experiments and when was included was written in different ways (see supplementary material for details in https:// osf.io/hu9wm/). Previous studies have shown that the consequences of inequality are different when focusing on those who have more versus those who have less (Bruckmüller, Reese, & Martiny, 2017). In particular, asking participants how wealthy they felt may have triggered a comparison with the richest group.…”
Section: Discussionmentioning
confidence: 99%
“…But the questions about how poor they felt their ingroup to be was not included in all the experiments and when was included was written in different ways (see supplementary material for details in https:// osf.io/hu9wm/). Previous studies have shown that the consequences of inequality are different when focusing on those who have more versus those who have less (Bruckmüller, Reese, & Martiny, 2017). In particular, asking participants how wealthy they felt may have triggered a comparison with the richest group.…”
Section: Discussionmentioning
confidence: 99%
“…Also relevant to the likelihood of people taking social action on this issue is how descriptions of inequality are framed. Bruckmüller, Reese, and Martiny () have shown that relatively subtle variations in such framing, such as whether an advantaged group is described as having more or a disadvantaged group is described as having less, influence perceptions of the legitimacy of these differences; larger differences between groups were evaluated as less legitimate when the disadvantaged group was described as having less. Perceptions of the illegitimacy of inequality in group outcomes are likely to evoke group‐based anger, which in turn is known to be one of the predictors of collective action (Van Zomeren, Spears, Fischer, & Leach, ).…”
Section: Prospects For Social Changementioning
confidence: 99%
“…Focusing on one side or another has different effects on how people understand and react to inequality. For instance, framing economic inequality as people having more than the average (e.g., the rich have more than…) led conservatives to support heavier taxation for the rich ( Chow and Galak, 2012 ), average individuals to delegitimize economic inequality ( Bruckmüller et al, 2017 ) and support measures that take more resources from the rich ( Lowery et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%